Kryzys demokracji przedstawicielskiej zwiastunem końca Unii Europejskiej? - Scheffs, Łukasz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This article explores the role that legitimacy plays in EU. It begins by defining what democratic legitimacy means in the context of policy. The article argues for a broader understanding of legitimacy, based upon of the relationship between political information and political participation. The article then goes on to explore the extent to which democratic legitimacy exists at the European level and at the national level. The article concurs with existing assessments of European sources of legitimacy, namely that is a very little legitimization. This article asks what the role played by democratic legitimacy and what this legitimization can tell us about the nature of EU politics